Monetary Policies for Developing Countries : The Role of Corruption - Huang, Haizhou (IMF Working Papers; Working Paper ;, 2003)
This paper examines the role of corruption in the design of monetary policies for developing countries in a framework of fiscal and monetary interaction and obtains several interesting results. First, pegged exchange rates, currency boards, or dollarization, while often prescribed as a solution to the problem of a lack of credibility for developing countries, is typically not credible in countries with serious corruption. Second, the optimal degree of conservatism for a Rogoff (1985)-type central banker is an inverse function of the corruption level. Third, either an optimally designed inflation target or an optimal-conservative central banker is preferable to an exchange rate peg, currency board, or dollarization.